2015
DOI: 10.1007/s11102-015-0642-9
|View full text |Cite
|
Sign up to set email alerts
|

Median nerve conduction studies and wrist magnetic resonance imaging in acromegalic patients with carpal tunnel syndrome

Abstract: The median nerves of acromegalic patients with CTS were enlarged and had impaired nerve conduction. This finding represents a predominant intrinsic feature in the pathophysiology of the disease rather than an extrinsic feature such as a thickened transverse carpal ligament.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 18 publications
3
16
0
Order By: Relevance
“…For both median and ulnar nerves, disease control was associated with a reduction of the area values (p = 0.02 and p = 0.002, respectively) [64]. These results seem to be confirmed by recent studies involving magnetic resonance imaging in the study of carpal tunnel among ACRO [65].…”
Section: Musculoskeletal Complicationssupporting
confidence: 73%
“…For both median and ulnar nerves, disease control was associated with a reduction of the area values (p = 0.02 and p = 0.002, respectively) [64]. These results seem to be confirmed by recent studies involving magnetic resonance imaging in the study of carpal tunnel among ACRO [65].…”
Section: Musculoskeletal Complicationssupporting
confidence: 73%
“…Decompression of the carpal tunnel is the most common hand surgery with approximately 460 000 procedures per year in the US and 300 000 in Germany [24,25]. Symptomatic CTS occurs in up to 64 % of acromegaly patients [26][27][28][29][30][31] although only 6 % of acromegaly diagnoses are triggered by CTS [32]. Retrospective data, however, showed, that up to 20 % of patients underwent surgery for CTS years before acromegaly was diagnosed (unpublished results).…”
mentioning
confidence: 99%
“…Previous studies have reported that approximately four‐fifths of patients with acromegaly have subclinical abnormalities on electrodiagnostic tests, and up to 64% have symptomatic CTS. Although a substantial improvement in symptoms has been seen when the growth hormone levels are diminished, the exact physiopathologic mechanism has not been clarified . An increase in the size of the median nerve or cross‐sectional area has been studied with both magnetic resonance imaging and US .…”
Section: Discussionmentioning
confidence: 99%
“…Although a substantial improvement in symptoms has been seen when the growth hormone levels are diminished, the exact physiopathologic mechanism has not been clarified. [1][2][3]12 An increase in the size of the median nerve or cross-sectional area has been studied with both magnetic resonance imaging and US. 8,12,13 Ultrasound imaging has shown swelling of the nerve proximal to the entrapment site, 7,10 and magnetic resonance imaging has shown increased signal intensity on T2-weighted images.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation